PENGARUH PENGGUNAAN MEDIA DIORAMA TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA DINI (Penelitian Kuasi Eksperimen di Kelompok B RA Al Patwa Cicukang Kabupaten Bandung) - Ade Novi Siti Nurhayati; yuyun yulianingsih; arif nursihah (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This study was motivated by the low fine motor skills of early childhood group B in RA Al Patwan, such as children who have not been able to do writing, holding pencils and scissors. The objectives of this study are 1.) to determine the fine motor skills of group B children in RA Al Patwa using diorama media (Experimental Group), 2.) to determine the fine motor skills of Group B children in RA Al Patwa using flannel board media (Control Group), 3.) to determine the difference in the use of diorama media and flannel board on fine motor skills of group B children in RA Al Patwa. This study used a quantitative approach through experimental methods with nonequivalent control group design. The subjects in this study were group B children in RA Al Patwa with a sample of 30 children. The data collection techniques used are observation, interviews, and documentation. Data analysis techniques use validity tests, reliability tests, normality tests, homogeneity tests, and hypothesis tests. The results showed that the fine motor skills of group B children in RA Al Patwa after using diorama media showed an average score in the experimental group when pretest 39 with failed qualifications and posttest of 75 with good qualifications. While the average score of the control group during the pretest was 41 with failed qualifications and posttest in the experiment was 69 with sufficient qualifications. The results on the t-test show a calculated t value of 17.789 greater than the table t of 2.048 which means Ha is accepted and Ho is rejected. This shows that there is a significant effect with the use of diorama media on the fine motor skills of group B children in RA Al Patwa.